Urgent Problems of the Pension Fund of Ukraine - Tulai Oksana I. (Problemi Ekonomiki, 2016)
The current state and problems of the Pension Fund of Ukraine have been highlighted. The formation of the budget of this financial institution has been analyzed. It is emphasized that the effective functioning of the Pension Fund of Ukraine is an important condition for sustainable human development, and in view of this factors influencing the process of its improvement have been identified. Firstly, this is a decrease in the number of the working population against the increase in the number of pension recipients, which directly affects the system of mandatory pension insurance. It is found that the effectiveness of the latter can be guaranteed by two conditions: excess of the working population over the number of persons of retirement age and fair payment of insurance premiums. Secondly, it is the population age structure. In this context it is noted that for our state it is economically advantageous to have a lot of working pensioners because they themselves form the pension they receive. Thirdly, it is the level of remuneration. A serious aspect of the problem is the shadowing of incomes and shifting of personal responsibility for the own well-being to the state. Therefore, it is proposed at the legislative level to develop a procedure of a gradual increase of wages and raising the share of the latter in the cost of goods or services. Fourthly, it is a low level of income among the majority of people of retirement age. Therefore, as an alternative source of rising funds for making pension payments there determined an accumulation system of mandatory pension insurance. Fifth, it is the differentiation of the rate of pension payments. It is claimed that the rate of pension should be the same for the people who paid equal premiums. It is important to take into account interests of all participants in the pension system — payers of insurance premiums, recipients of pension and social aid, as well as the state with the Pension Fund of Ukraine being its authorized representative